PRAGMATICS AND CHARACTER LANGUAGE BUILDING - Jumanto, - (FEB UNTAG Semarang, 2012)
This opinion paper is about how to build a character language through pragmatics. The main aspects of pragmatics are briefly introduced and then elaborated as building-blocks for building a character language. The building blocks are: (1) elaboration of meaning and form strategies, (2) distant language and close language strategies, (3) politeness and camaraderie strategies, (4) object language and metalanguage strategies. The character language building through pragmatics is a verbal social project carried out in 6 phases: (1) interaction phase, (2) teaching-and-learning process phase, (3) evaluation phase, (4) re-evaluation phase, (5) verification phase, (6) selection phase. Upon the completion of a character language building, a competent speaker is well-equipped for using language in a particular situation that may call.